The role of the dementia specialist nurse in acute care: a scoping review. Issue 9 (3rd December 2014) - Griffiths, Peter; Bridges, Jackie; Sheldon, Helen; Thompson, Rachel
Abstract : Aims and objectives: To identify the potential benefits of dementia specialist nursing and to inform the implementation of roles to support people with dementia during hospital admission. Background: Extended stays and adverse events mean that hospital admissions are costly for people with dementia, and patient experiences and outcomes can be poor. Specialist nurses have been identified as having potential to enhance care quality, reduce excess stays and reduce costs, but the evidence base for dementia specialist nurse roles has not previously been synthesised. Design: Scoping review. Data sources: Cochrane Library, Campbell Collaboration, Clinical Evidence, Evidence‐Based Medicine, York Centre for Reviews and Dissemination, PubMed, Medline, CINAHL and PsycInfo databases and internet searches and personal libraries/expert consultation to identify grey literature. Methods: Initial scoping searches were used to inform more focused systematic searches. Studies directly evaluating dementia nurse specialist roles or giving evidence of effectiveness of interventions/services that could be delivered by them to improve core outcomes were identified by one reviewer and verified by a second reviewer. Results: While direct evidence for the effectiveness of these roles is lacking, a number of areas were identified in which a nurse specialist role could make a contribution, including preventing adverse events and improving patient experiences and outcomes. There is a considerable body of evidence for the effectiveness of these interventions although the volume of evidence for specific interventions is not always significant. Conclusions: The evidence indicates that a skilled dementia specialist nurse, undertaking a clearly defined role, and working directly with people with dementia and their carers for a significant proportion of the time, could benefit people with dementia in hospitals and their family carers. Relevance to clinical practice: Clear guidance for the development and implementation of dementia specialist nurse roles in acute hospital settings.